Emergencies in Neuromuscular Disease - Agostoni, Elio (Emergency Management in Neurology, 2017)
This book offers a practical tool for handling neuromuscular emergencies, and is divided by the main neuromuscular diseases on the basis of their anatomical and clinical location: diseases affecting the anterior horn of the spinal cord (tetanus), those that affect the nerve roots and nerves (SGB, multiple mononeuritis, porphyria), the neuromuscular junction (MG and botulism) and, lastly, muscle pathologies (rhabdomyolysis, malignant hyperthermia, periodic paralysis). It provides updated diagnostic/therapeutic protocols and decision-making algorithms for each pathology, and examines a range of scenarios on the basis of clinical cases. Emergencies in Neuromuscular Disease will be of interests for a wide variety of specialists including neurologist, neurophysiologists and anesthesiologists.